Métal Hurlant - Jin, Huaqing (France, 2009)
For more than twenty years, tons and tons of metallic and electronic waste from all around the world has been transported to a Chinese town called Fengjang, in the south of Shanghai. Around 50,000 migrant workers have formed a real army to dismantle these metallic wastes. These "green soldiers" decompose, cut, split and recycle, with the most rudimentary means, almost 2 million tons of garbage every year. To remain and assume the minimum materials that is theirs, they work hard, bear an incredible precariousness and put in danger their own health due to the simply unacceptable working conditions.
Verzio Film Festival Submission
Keywords: Documentary films